Evaluasi Sifat Tanah Pada Beberapa Teknik Konservasi Tanah dan Air di Perkebunan Kelapa Sawit - Saroha Manurung (Jurnal Agro Estate, 2017)
Evaluation o f Soil properties In Some Soil and Water Concervation Techniques in Oil Palm Plantation. The purpose of this study to determine the most appropriate concervation tecniques used in oil palm plantations in the repair o fsoilproperties. This study was conductedfrom April 2013 to February 2014 in the Bangun Estate, PTPN III Simalungun district, North Sumatra Province. This study using a randomized block desing (RBD) no factorial with treatment factors, consisting of; VM: Vertical Mulch, CB: Compost Biopori, CD: Concave Disc, PG: Planting Grass. The results show (1) the treatment of concervation techniques concave disc with compost bioporifound significant effect on soil water content. The best treatment to the amount o f moisture contained in the compost treatment biopori. (2) In the treatment of concervation techniques for disk concave vertical mulcing, planting grass, compost treatment andplanting grass, bioporifound a real influence on the permeability of the soilprofil, which in the best treatment to the permeability of the soil profile contained in the treatment ofgrass planting. (3) The treatment technique implemented concervation in oil palm plantation did not significantly affect organic C, Total-N, C/N, Bilk Density, infiltration, levels of N, P, K in the leaves.